Application of dynamic simulations in the analysis of measures for improving energy efficiency of buildings - Dragićević, Snežana M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
One of the most commonly used methods for improving energy performances of buildings is reducing heating energy consumption. This paper shows a comparative analysis of building energy demand for space heating based on case studies in which building modifications were made with insulating materials of building envelopes and with different window types. For the analysis, a public building with 6 floors, located in Belgrade, was selected. For a dynamical simulation and evaluation of the applied energy efficiency measures to reduce heating energy consumption, the DesignBuilder program was used. The results show that the insulation of the building and the replacement of windows can lead to an annual reduction of heating energy up to 61%. Introduction In this paper, some of the most effective methods for improving energy performances of buildings are analyzed. It examines the influence of methods of building revitalization at the building level with the use of: - Thermal insulation of external walls, and - Windows with multiple glazing filled with gas in order to ensure keeping heat indoors during winter, but also to prevent excessive energy gains during summer. The aim of the paper is to show that, with a dynamic building simulation of building thermal behavior, it is possible to calculate energy requirements for heating, recognizing the differences between energy performances of buildings in different variants. In this regard, a comparative analysis of energy needs obtained using different types of external walls insulation and glazing will be carried out. The analysis will be performed in a case study for a public object located in Belgrade. Measures for improveming energy efficiency in buildings The most commonly used methods for energy revitalization of buildings is the insulation of exterior walls, ie. building envelope (Young, Altan, 2013). The thickness and quality of the building envelope have a significant impact on the amount of heat that is lost through walls. In the case of non-performing insulation, additional heat losses in winter and the possibility of condensation on interior walls occur, as well as excessive consumption of energy for cooling in summer. The most commonly used insulating materials are expanded polystyrene - Styrofoam (EPS) and extruded polystyrene (XPS). Regardless of which type of exterior walls insulation is used, its thickness has a significant impact on heat losses. Nowadays, the minimum insulation thickness of 10 cm is recommended. In the process of building energy rehabilitation, windows are an important segment because they usually occupy a large area of ​​the building envelope, which is common in office buildings. Today, high-quality windows with triple low-e glass panes are used more and more, allowing a significant reduction of costs for space heating (Apte et al., 2003). Results of the dynamic simulation An energy calculation was applied for a public office building, located in Belgrade. The building has six floors with a space area of 675 m2. (Figure 1). The simulation was performed, followed by calculating heating energy consumption for two types of external walls, insulating materials with different thicknesses and with different types of window glazing. The proposed simulations were performed for the same configuration of the building, in the same period of time, but with a series of successive modifications. The simulated model of the building represents the transformation of an existing reference object into a low-energy building. The simulation results show that the application of measures to increase the building energy efficiency by installing insulation of a thickness of 5 cm on external walls do not give satisfactory results. The obtained results show that the application of extruded polystyrene of 10 cm in thickness gives the best results. The comparison of the heating energy consumption for the building without insulation and for the building insulated with 10 cm of expanded polystyrene and extruded polystyrene shows that it is possible to achieve annual energy saving up to 55%. The comparison of the application effects of 10 cm-thick insulation shows that 3.7% of energy could be saved annually for heating if extruded polystyrene is used instead of expanded polystyrene. Figure 3 presents a comparative analysis of heating energy consumption for the reference building and the building insulated with 10 cm-thick extruded polystyrene, as well as for the cases when the building has double and triple glazing windows. Based on these results, it can be concluded that due to the replacement of double glazing windows with triple ones, saving of 17% of annual heating energy consumption could be obtained. Conclusion This paper presents a dynamic simulation of the energy behavior of the analyzed object and a comparative analysis between the reference object and the presented alternative solutions, which represent an object with applied various measures to improve its energy efficiency. Based on these results, it can be concluded that the insulation of external walls with 10 cm-thick expanded polystyrene or extruded polystyrene results in energy saving of about 55% compared to the reference variant of the building. For such an insulated object, if double-glazing windows are replaced with with energy-efficient triple-glazing windows, energy saving of about 61% compared to the reference variant of the building can be achieved. The results clearly show the validity of the presented measures to increase the energy efficiency of the object in question.